Marketmaking Middlemen - Pieter A. Gautier; Bo Hu; Makoto Watanabe (Institute for the Study of Labor (IZA), 2016)
This paper develops a model in which market structure is determined endogenously by the choice of intermediation mode. We consider two representative business modes of intermediation that are widely used in real-life markets: one is a middleman mode where an intermediary holds inventories which he stocks from sellers for the purpose of reselling to buyers; the other is a market-making mode where an intermediary offers a platform for buyers and sellers to trade with each other. In our model, buyers and sellers can simultaneously search in an outside market and use the intermediation service. We show that a marketmaking middleman, who adopts the mixture of these two intermediation modes, can emerge in a directed search equilibrium.
Keywords: D4; G2; L1; L8; R1; 330; middlemen; marketmakers; platform; directed search